l‑Asparaginase from Solanum lycopersicum as a Nutraceutical for Acute Lymphoblastic Leukemia - Khabade, Sarina P.; Sirigiri, Divijendra Natha Reddy; Ram, Anshu Beulah (ACS omega, 2024)
l-Asparaginase (E.C. 3.5.1.1) is an indispensable analeptic anticancer enzyme used as an amalgam with additional cancer medicines for the cure of acute lymphoblastic leukemia (ALL). The presence of lAparaginase in tomato was confirmed byWestern blotting and DNA sequencing. The l-Asparaginase gene from tomato has been deposited in the NCBI database with accession number: OR736141. Crude enzyme was extracted from the fruit pulp of Solanum lycopersicum, and the activity was determined by the Nesslerization method. Further, the crude extract was subjected to purification, and kinetic parameters were studied. The percentage yield was calculated to be 6.457, and the purification fold was 0.086. The enzyme showed maximum activity at optimum pH 7.0, optimum temperature 37 °C, and incubation time of 05 min. The Michaelis constant “K m” and maximum velocity “V max” values were determined by the Lineweaver–Burk plot, which showed a low K m value of 0.66 and V max of 3.846 IU. Cytotoxic studies were carried out for crude and purified l-asparaginase. Purified l-Asparaginase has exhibited anticancer activity against the ALL model system, K-562 cell line, comparable to that of the anticancer compound vinblastine. Hence, l-Asparaginase from the fruit extract of tomato could be used as a nutraceutical to support cancer treatment in acute lymphoblastic leukemia.